2021
DOI: 10.3389/fpsyt.2020.608588
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Resilience, Mental Health, and Inhibitory Control Among Youth and Young Adults Under Stress

Abstract: Psychological resilience allows one to cope successfully with adversities occurring during stressful periods, which may otherwise trigger mental illness. Recent models suggest that inhibitory control (IC), the executive control function which supports our goal-directed behavior and regulates our emotional response, may underlie resilience. However, the ways in which this is manifested during stressful situations in real life is still unclear. Here, we examined the relationship between IC, psychological resilie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 96 publications
2
17
1
Order By: Relevance
“…Our findings are consistent with studies reporting no gender on psychological resilience, hence showing no greater vulnerability in female soldiers under stressful conditions compared to their male counterparts (17). Specifically, these lack of gender differences in resilience in our sample may be associated with the high motivation of female recruits in the mixed-gender units in IDF, for which female soldiers may volunteer but service is mandatory for male soldiers [see elaboration in (63)]. Thus, the Israeli female soldiers who serve in these units are possibly more motivated to serve in a combat occupation and environment, and hence show relatively high levels of general predisposition trait resilience.…”
Section: Gender Differences and Their Contribution To Qol Predictionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings are consistent with studies reporting no gender on psychological resilience, hence showing no greater vulnerability in female soldiers under stressful conditions compared to their male counterparts (17). Specifically, these lack of gender differences in resilience in our sample may be associated with the high motivation of female recruits in the mixed-gender units in IDF, for which female soldiers may volunteer but service is mandatory for male soldiers [see elaboration in (63)]. Thus, the Israeli female soldiers who serve in these units are possibly more motivated to serve in a combat occupation and environment, and hence show relatively high levels of general predisposition trait resilience.…”
Section: Gender Differences and Their Contribution To Qol Predictionsupporting
confidence: 91%
“…In the current study, we include the results of the self-report data collected during t0 and the QoL data collected during t1, as well as the mood data collected during the 2 weeks of the tracking period. Data from other aspects of the trial are reported elsewhere ( 63 ).…”
Section: Methodsmentioning
confidence: 99%
“…Psychological frailty may result from aging-related deficits in psychological resilience and brain reserves. Psychological resilience refers to the capacity of an individual to cope in the face of stressors and adversity, allowing individuals to successfully maintain their physical and mental health (Afek et al, 2021; Fletcher & Sarkar, 2013). Brain reserve is defined as the ability of an individual to withstand aging-associated and pathological changes to the brain, also known as resilience of the brain (Fratiglioni & Wang, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…When a high probability instance is connected through a dependency relationship, a path is formed that is the Zero-Day attack path. The paper [13], describe a system developed to extract necessary signatures and an algorithm to solve this problem. The algorithm finds the length of messages.…”
Section: Literature Reviewmentioning
confidence: 99%